Care for Patients With Neuromuscular Disorders in the COVID-19 Pandemic Era - Tseng, Yung-Hao; Chen, Tai-Heng (Frontiers in Neurology, 2021)
The coronavirus-19 (COVID-19) pandemic has prompted a rapid and unprecedented reorganization of medical institutions, affecting clinical care for patients with chronic neurological diseases. Although there is no evidence that patients with neuromuscular disorders (NMD) confer a higher infection risk of COVID-19, NMD, and its associated therapies may affect the patient's ability to cope with infection or its systemic effects. In particular, as respiratory compromises account for the major cause of mortality and morbidity in NMD patients, newly emerging data also show that the risk of exacerbation caused by COVID-19 accumulates in this particular patient group. Several neurological associations and neuromuscular networks have recently guided the impact of COVID-19 on patients with NMD, especially in managing cardiopulmonary involvements. It is recommended that patients with moderate to high-risk NMD be sophisticatedly monitored to reduce the risk of rapid decline in cardiopulmonary function or potential deterioration of the underlying NMD. However, limited neuromuscular-specific recommendations for NMD patients who contract COVID-19 and outcome data are lacking. There is an urgent need to properly modify the respiratory care method for NMD patients, especially during the COVID-19 pandemic. Conclusively, COVID-19 is a rapidly evolving field, and the practical guidelines for the management of NMD patients are frequently revised. There must be close collaboration in a multidisciplinary care team that should support their hospital to define a standardized care method for NMD patients during the COVID pandemic. This article reviews evidence-based practical guidelines regarding care delivery, modification, and education, highlighting the need for team-based and inter-specialty collaboration.